On (g,s)-Continuous and (π g,s)-Continuous Functions - Ekici, Erdal (Sarajevo Journal of Mathematics, 2024)
New generalizations of contra-continuity called (π g,s)-continuity and (g, s)-continuity are presented. Characterizations and properties of (π g,s)-continuous functions are discussed. 2000 Mathematics Subject Classification. 54C05, 54C08